Retention of BioAggregate and MTA as coronal plugs after intracanal medication for regenerative endodontic procedures: an ex vivo study - Suzan Abdul Wanees Amin; Shaimaa Ismail Gawdat (Restorative Dentistry & Endodontics, 2018)
ObjectivesThis study compared the retention of BioAggregate (BA; Innovative BioCeramix) and mineral trioxide aggregate (MTA; Angelus) as coronal plugs after applying different intracanal medications (ICMs) used in regenerative endodontics.Materials and MethodsOne-hundred human maxillary central incisors were used. The canals were enlarged to a diameter of 1.7 mm. Specimens were divided into 5 groups (n = 20) according to the ICM used: calcium hydroxide (CH), 2% chlorhexidine (CHX), triple-antibiotic paste (TAP), double-antibiotic paste (DAP), and no ICM (control; CON). After 3 weeks of application, ICMs were removed and BA or MTA were placed as the plug material (n = 10). The push-out bond strength and the mode of failure were assessed. The data were analyzed using 2-way analysis of variance, the Tukey's test, and the χ2 test; p values < 0.05 indicated statistical significance.ResultsThe type of ICM and the type of plug material significantly affected bond strength (p < 0.01). Regardless of the type of ICM, BA showed a lower bond strength than MTA (p < 0.05). For MTA, CH showed a higher bond strength than CON, TAP and DAP; CHX showed a higher bond strength than DAP (p < 0.01). For BA, CH showed a higher bond strength than DAP (p < 0.05). The mode of failure was predominantly cohesive for BA (p < 0.05).ConclusionsMTA may show better retention than BA. The mode of bond failure with BA can be predominantly cohesive. BA retention may be less affected by ICM type than MTA retention.